Structural Overview and Morphotectonic Evolution of a Strike-Slip Fault in the Zone of North Almora Thrust, Central Kumaun Himalaya, India. (7th February 2016) - Joshi, Lalit M.; Pant, Pitamber D.; Kotlia, Bahadur S.; Kothyari, Girish C.; Luirei, Khayingshing; Singh, Anoop K.
Abstract : The aim of the present research is to provide the base line details of the NNW-SSE trending Raintoli fault (RF) which is running parallel to the North Almora Thrust (NAT) along the Saryu valley from Seraghat-Naichun to Seri in the central sector of the Uttarakhand Himalaya, India. The RF is characterized as dextral strike slip fault and behaves as a ductile shear zone within the zone of NAT. The dextral sense of shear movement of RF is delineated by the fabric of the shear zone rocks including microscopically observed indicators such as sigma and delta porphyroclasts, quartz c -axis, and the field structural data. Additionally, in the quaternary period the dextral strike slip fault is reactivated with oblique slip component as characterized by various geomorphic indicators, for example, triangular facets, abandoned river channels, unpaired fluvial terraces, and V-shaped valleys with recurrent seismicity. Further, the morphometric parameters including Valley Floor Width to Valley Height (V f ), asymmetry factor (AF), and gradient index (GI) further prove active nature of RF as suggested by low values of hypsometric integration, V-shaped valley, higher gradient index, and tilting of Saryu basin.